Analysis of Value Proposition Canvas and Lean Business Canvas for the Development of Marketing, Operational and Human Resource Strategies in EDU Smarty Generation Tutoring in Tangerang – Indonesia - Trisulo Muljopamudji; Difka Sabila Rasyad; Anggiat Huminsa FST; Unggul Kustiawan; M. Dhafi Iskandar; Edi Hamdi (Jurnal Indonesia Sosial Teknologi, 2025)
This study aims to analyze the use of Value Proposition Canvas (VPC) and Lean Business Canvas (LBC) in developing marketing, operational, and human resource (HR) strategies for EDU Smarty Generation tutoring center in Tangerang, Indonesia. Based on VPC analysis, a deeper understanding of the students' needs, problems, and desires was gained, which helped in designing a more focused marketing strategy. Through LBC, it was found that the business model of EDU Smarty Generation emphasizes the flexibility of blended learning and online self-learning independence to cater to the diverse needs of students. The study also identified the importance of HR development to support the implementation of these strategies, including enhancing teacher skills and effectively utilizing technology. The findings show that applying these two frameworks can improve the effectiveness of marketing, operational, and HR strategies and contribute to the long-term growth of EDU Smarty Generation.